Memahami Konsep Ajaran Doketisme - Albertus O. Boimau; Aben T. Banamtuan; Mozes Lawalata (International Forum of Researchers and Lecturers, 2024)
Docetism is a term that states that Jesus Christ was not truly human, but only appeared to be human. This word comes from the Greek